2018
DOI: 10.1186/s12889-017-4999-8
|View full text |Cite
|
Sign up to set email alerts
|

Youth paying for sex: what are the associated factors? Findings from a cross-sectional study in Cambodia

Abstract: BackgroundAt-risk male youth in Cambodia who purchase sex are at greater risk for HIV compared to the general population. Factors associated with paying for sex among youth are poorly studied, both globally and in Cambodia. This study aimed to identify specific factors associated with transactional sex with women among most-at-risk male youth in Cambodia.MethodsThis cross-sectional questionnaire survey was conducted with 405 sexually active male youth aged 16–24 recruited at ‘hotspots’ in the capital city of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
2
21
1
3
Order By: Relevance
“…Frequency of listening to radio was also categorised as not at all = 1, less than once a week = 2, at least once a week = 3 and almost every day = 4. The choice of these explanatory variables was based on previous studies ( Belza et al, 2008 ; Carael, Slaymaker, Lyerla, & Sarkar, 2006 ; Dizechi et al, 2018 ; Jones et al, 2015 ; Regushevskaya, Haavio-Mannila, & Hemminki, 2013 ; Schei & Stigum, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequency of listening to radio was also categorised as not at all = 1, less than once a week = 2, at least once a week = 3 and almost every day = 4. The choice of these explanatory variables was based on previous studies ( Belza et al, 2008 ; Carael, Slaymaker, Lyerla, & Sarkar, 2006 ; Dizechi et al, 2018 ; Jones et al, 2015 ; Regushevskaya, Haavio-Mannila, & Hemminki, 2013 ; Schei & Stigum, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed that socio-demographic, economic and behavioral factors are associated with paid sex among men. The socio-demographic factors include age ( Girchenko et al, 2015 ; Jewkes et al, 2012 ; Rich et al, 2018 ; Rissel et al, 2017 ), educational level ( Choudhry et al, 2015 ; Dizechi et al, 2018 ; Galvan, Ortiz, Martinez, & Bing, 2009 ; Jewkes et al, 2012 ; Pitts, Smith, Grierson, O'brien, & Misson, 2004 ), place of residence ( Balekang and Dintwa, 2016 , Dizechi et al, 2018 , Pan, Parish, & Huang, 2011 ) marital status ( Belza et al, 2008 ; Rissel et al, 2017 ; Schei & Stigum, 2010 ; Ward et al, 2005 ) and wealth status ( Dizechi et al, 2018 ; Jewkes et al, 2012 ; Jones et al, 2015 ; Rich et al, 2018 ). It has also been found that exposure to mass media (newspapers, magazines, radio and television) are associated with risky sexual practices, which may include paid sex ( Asekun-Olarinmoye, Asekun-Olarinmoye, Adebimpe, & Omisore, 2014 ; Bleakley, Hennessy, Fishbein, & Jordan, 2011 ; Fisher, Hill, Grube & Grube, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical violence and bodily harm to women, verbal harm, and violence, not paying the agreed money, and even theft of women's money, along with forced sex, involuntary unusual sexual relationship, group sex by force, compulsion not to use protective and prophylactic devices are some aspects of the violence which prostituted women in this study mentioned. Various studies have shown that violence against prostituted women is a common phenomenon [ 25 , 26 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Farley M et al., 2004 and Scorgie F et al., 2013 showed that violence against prostituted women is a norm and sexual and physical harassment, verbal humiliation, and torturing are forms of this violence [ 14 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the vast literature on sex work, most studies to date have focused exclusively on female sex workers (812). Although a few studies have focused on MSW and the risk of HIV/STI transmission (13,14,2,15,16), research on male clients of MSW is very scarce (1720).…”
Section: Introductionmentioning
confidence: 99%